Health Systems Resilience in the Caribbean : 360° Resilience Background Paper - Khan, Alyssa; Harnam, Neesha (World Bank, Washington, DC, 2021)
Caribbean islands are vulnerable to external shocks such as natural disasters, disease outbreaks, and economic decline due to their geographic location, geologies, and economic structures. Most Caribbean countries have small-scale economies that are highly dependent on climate-related activities such as tourism and agriculture. Shocks can therefore have devastating impacts on individuals and communities, and stymie development efforts. Health system resilience (HSR) refers to the capacity of a health system to prepare for and effectively respond to shocks, such as natural disasters and disease outbreaks. While there are important differences between the risks posed by natural disasters and disease outbreaks, both types of hazards have the potential to cripple multiple facets of the health sector at a time of increased demand for health services. As a result, population health outcomes may be adversely affected. Thus, increasing the resilience capacity of a health system ultimately reduces the negative impacts of shocks on population health.